2023
DOI: 10.1093/evolut/qpad071
|View full text |Cite
|
Sign up to set email alerts
|

Variation in density, immune gene suppression, and coinfection outcomes among strains of the aphid endosymbiont Regiella insecticola

Abstract: Many insects harbor heritable microbes that influence host phenotypes. Symbiont strains establish at different densities within hosts. This variation is important evolutionarily because within-host density has been linked to the costs and benefits of the symbiosis for both partners. Studying the factors shaping within-host density is important to our broader understanding of host-microbe coevolution. Here we focused on different strains of Regiella insecticola, a facultative symbiont of aphids. We first showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In fact, we found that aphids harboring one strain of R. insecticola (.CF7) appear to be more susceptible to B. apiculata infection. This strain comes from a specific clade of Regiella (referred to as 'clade 2' in the literature [24]) that we have found establishes at extremely high densities within hosts [26] by suppressing aphid innate immune genes like Phenoloxidase [17,29]. One possibility is that reduced expression of Phenoloxidase, which is an important component of aphid immunity to fungal pathogens [30,31], makes aphids more susceptible to fungal pathogens like B. apiculata in the absence of symbiont mediated protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we found that aphids harboring one strain of R. insecticola (.CF7) appear to be more susceptible to B. apiculata infection. This strain comes from a specific clade of Regiella (referred to as 'clade 2' in the literature [24]) that we have found establishes at extremely high densities within hosts [26] by suppressing aphid innate immune genes like Phenoloxidase [17,29]. One possibility is that reduced expression of Phenoloxidase, which is an important component of aphid immunity to fungal pathogens [30,31], makes aphids more susceptible to fungal pathogens like B. apiculata in the absence of symbiont mediated protection.…”
Section: Discussionmentioning
confidence: 99%
“…We collected fungal entomopathogens from field aphids in Knoxville, TN, in 2022 and used molecular techniques to determine the species of each fungal isolate. We then established a panel of aphids that each had the same host genotype with a single infection of a facultative symbiont including strains of Regiella and Spiroplasma that we have found to be protective against P. neoaphidis [15][16][17] and Serratia symbiotica, which confers no protection against P. neoaphidis. We found that aphid facultative symbionts do not protect against B. apiculata, and we discuss these results within the context of aphid-symbiont-pathogen coevolution.…”
Section: Introductionmentioning
confidence: 99%
“…We screened the line for the seven species of facultative symbionts found in aphids using established PCR protocols [ 41 , 42 ]. For this screen, we extracted DNA using ‘Bender buffer’ and ethanol precipitation as in previous studies [ 43 , 44 ]. We then used PCR with species-specific primers [ 42 , 45 ] to screen for Hamiltonella defensa, Fukatsuia symbiotica (previously referred to as X-type), Regiella insecticola , Rickettsia sp., Ricketsiella sp., Serratia symbiotica , and Spiroplasma sp.…”
Section: Methodsmentioning
confidence: 99%